2007
DOI: 10.1186/1471-2334-7-48
|View full text |Cite
|
Sign up to set email alerts
|

Higher incidence of persistent chronic infection of Chlamydia pneumoniae among coronary artery disease patients in India is a cause of concern

Abstract: Background: There is growing evidence that Chlamydia pneumoniae may be involved in the pathogenesis of atherosclerosis, as several studies have demonstrated the presence of the organism in atherosclerotic lesions. C. pneumoniae infections, which are especially persistent infections, have been difficult to diagnose either by serological methods or isolation of the organism from the tissue. Nucleic Acid Amplification tests (NAATs) has emerged as an important method for detecting C. pneumoniae. Inspite of high pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 30 publications
4
16
1
Order By: Relevance
“…Their significant induction in patients with atherosclerosis compared to healthy individuals proposing that cells from atherosclerotic patients may specifically recognize these antigens suggesting the presence of chlamydia in patients with atherosclerosis as previously demonstrated [13] . This was confirmed by the absence of significant difference between patients and healthy subjects in all examined chemokines when using PHA as a positive control.…”
Section: Resultssupporting
confidence: 57%
See 1 more Smart Citation
“…Their significant induction in patients with atherosclerosis compared to healthy individuals proposing that cells from atherosclerotic patients may specifically recognize these antigens suggesting the presence of chlamydia in patients with atherosclerosis as previously demonstrated [13] . This was confirmed by the absence of significant difference between patients and healthy subjects in all examined chemokines when using PHA as a positive control.…”
Section: Resultssupporting
confidence: 57%
“…A number of risk factors for atherogenesis, including infectious agents, have been shown to exert their influence via inflammatory means. There is a growing evidence that Chlamydia pneumoniae (C. pneumoniae) may be involved in the pathogenesis of atherosclerosis, as several studies have demonstrated the presence of the organism in atherosclerotic lesions [13] . C. pneumoniae can initiate and propagate inflammation in ways that could contribute to atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…This becomes significant when one considers that a history of being infected with influenza A or B (determined by the presence of IgG antibodies) is associated with an increased risk of myocardial infection [39] . Another pathogen that has been associated with the development of CV disease is Chlamydia pneumonia [40] . Other pathogens that have been linked to CAD include Mycoplasma pneumonia and Helicobacter pylori.…”
Section: Other Infections As Risk Factorsmentioning
confidence: 99%
“…However, recent reports (both serological studies and studies of outbreaks in confined populations [43,44]) show that it is still a widespread and successful respiratory pathogen. In addition to respiratory infections, C. pneumoniae has been linked with several other chronic conditions, most notably cardiovascular inflammatory diseases such as atherosclerosis, abdominal aortic aneurisms, and valvular lesions (45)(46)(47)(48). While there is a body of published evidence linking C. pneumoniae and cardiovascular disease, a causal link remains to be definitively proven and is considered controversial by some.…”
mentioning
confidence: 99%